Competing effects of rotational diffusivity and activity on finite-sized clusters. (15th June 2022) - Pilla, Ravi Thej; Mani, Ethayaraja
Abstract: Colloidal particles interacting via short-range attraction and long-range repulsion are known to stabilize finite-sized clusters under equilibrium conditions. In this work, the effect of self-propulsion speed (activity) and rotational diffusivity ( D r ) on the phase behavior of such particles is investigated using Brownian dynamics simulations. The system exhibits rich phase behavior consisting of clusters of different kinds. The cluster size varies non-monotonically with activity: increasing first and decreasing at higher activity, thus driving cluster-to-fluid phase transition. Rotational diffusivity also facilitates the formation of clusters. Larger clusters could be stabilized at low D r values while at high D r values, clusters are stable even at higher activities. The analysis of the static structure factor of the system confirms that rotational diffusivity delays the cluster-to-fluid transition driven by activity.